2006
DOI: 10.1055/s-2006-942757
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Clinicopathological Studies on Staging and Survival in Essential Thrombocythemia, Chronic Idiopathic Myelofibrosis, and Polycythemia Rubra Vera

Abstract: In chronic myeloproliferative disorders (MPDs), varying results regarding staging of disease and assessment of outcome have been reported. Risk classification is mainly based on clinical data; however, in those disorders associated with an elevated platelet count, discrimination of (true) essential thrombocythemia (ET) may be difficult without the possibility to recognize characteristic histopathological bone marrow patterns according to the World Health Organization (WHO) guidelines. Patients with ET reveal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 56 publications
(174 reference statements)
4
71
0
3
Order By: Relevance
“…The onset of the MPNs is often a very slowly advancing process and both in the WHO-defined PV and ET, disease-specific survival (loss in life expectancy) is not substantially different from that of a control population, especially in younger adults. 14 PMF is a more serious disease with expected median observed survival of about 6 years, 15 whereas in prefibrotic myelofibrosis median survival is about 10 years. 14 Information on the genetic abnormalities most commonly encountered in MPNs has to be explicitly discussed.…”
Section: How To Diagnose Mpn In Children and Young Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The onset of the MPNs is often a very slowly advancing process and both in the WHO-defined PV and ET, disease-specific survival (loss in life expectancy) is not substantially different from that of a control population, especially in younger adults. 14 PMF is a more serious disease with expected median observed survival of about 6 years, 15 whereas in prefibrotic myelofibrosis median survival is about 10 years. 14 Information on the genetic abnormalities most commonly encountered in MPNs has to be explicitly discussed.…”
Section: How To Diagnose Mpn In Children and Young Adultsmentioning
confidence: 99%
“…14 PMF is a more serious disease with expected median observed survival of about 6 years, 15 whereas in prefibrotic myelofibrosis median survival is about 10 years. 14 Information on the genetic abnormalities most commonly encountered in MPNs has to be explicitly discussed. The concern regarding the possibility that MPNs can be heritable should be addressed in this context by emphasizing that the vast majority of MPN cases are sporadic and that the genetic mutation of JAK2 is not a predisposing factor.…”
Section: How To Diagnose Mpn In Children and Young Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This trial investigates the effect of hydroxyurea versus anagrelide therapy, but particularly their influence on progression into MF in 809 patients with ET at high risk for vascular events. To highlight the impact of accurate morphological diagnosis on the development of MF, a corresponding multi-center study on 539 patients with high risk ET has been performed [128]. Clinical data at onset were in explicit accordance with the UK-PT 1 trial [129] as well as histological definitions that included manifest MF with at least Grade 2 on a threegraded scale [121].…”
Section: Primary Myelofibrosismentioning
confidence: 99%
“…Additional requirements were an increase in one grade in less than 12 months of follow-up together with at least two of the following: increase in spleen size of about 3 cm, unexplained decrease of hemoglobin, immature precursors in the peripheral blood and tear-drop poikilocytosis on the blood smear [27]. The overall incidence of myelofibrotic transformation after 36 months of observation time was 2.8% [128,129] according to the PVSG criteria [5,21], thus confirming the results of the UK-PT 1 study which reported a corresponding complication in 2.6% (21 of the 809 patients) [27]. However, when applying the WHO criteria for ET [1,2], not a single case revealed a transformation into MF either by clinical or morphological standards during observation time [128,129].…”
Section: Primary Myelofibrosismentioning
confidence: 99%